What Drives the Relationship Between Financial Flexibility and Firm Performance: Investment Scale or Investment Efficiency? Evidence from China. Issue 9 (1st September 2016) - Ma, Chun-Ai; Jin, Yanbo
ABSTRACT: Financial flexibility helps improve firm performance. By using data from Chinese listed companies, we examine whether investment scale or investment efficiency drives the relationship between financial flexibility and firm performance via a special mediator testing method that is widely used in the psychology literature (Baron and Kenny, 1986). We find that financial flexibility has a significant and positive effect on both investment and firm performance. However, investment scale rather than investment efficiency seems to drive firm performance. This finding helps us understand that Chinese companies tend to emphasize investment expansion more than they do investment efficiency to improve firm performance.